Hypertension best treatment options 2023 - Gonzalez, Guillermo Avalos; Garcia Santiago, Gerardo; Huerta Velazquez, Jose M.; Zepeda Torres, Jose M.; Jimenez Curriel, Alexa (International Journal of Advances in Medicine, 2023)
Systemic arterial hypertension is main cause of cerebrovascular events and coronary disease. Therefore, treatment and control of this disease is of great importance in public health. Arterial hypertension is a common disease that is defined as the persistent elevation of blood pressure more than 130/80 mm HG by the American college of cardiology (ACC)/American heart association (AHA), and by 8th joint national committee (JNC 8) criteria specify≥140/90 mmHg. The treatment of hypertension is based on non-pharmacological strategies and pharmacological. The best treatment for arterial hypertension is the combination of non-pharmacological strategies and pharmacological. We think that the most important step in a plan for primary care providers should be non-pharmacological strategies, principally the change of the diet of the patient, and encouraging them to lose weight and do physical activity daily. In the case of pharmacological strategies, as we saw in different studies and guidelines, all support the use of a combination of different medications. Because this way patients had better responses to treatment and decreased the rate of complications.